DENTAL HEALTH EDUCATION TO TEACHERS AND STUDENTS OF SD - IT AZZAHRA DEMAK IN THE ORDER OF IMPROVING KNOWLEDGE ABOUT MOUTH DENTAL HEALTH - Sugiarto, Febia Astiawati; Ardlina, Nira (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Basic Health Research data from the Ministry of Health of the Republic of Indonesia 2018 (RISKESDAS 2018) shows that the proportion of oral cavity diseases in Indonesia is still high, reaching 57.6%. When viewed by age, the proportion is 67.3% from the age of 5-9 years, and 55.6% from the age of 10-14 years. This shows that the proportion of oral cavity diseases in school-age children is quite high. Counseling and training on dental and oral health is a learning process aimed at teachers or parents in order to increase the degree of dental and oral health in children to the maximum.Method: Counseling and training of elementary school teachers as dental health cadres, Implementation of interactive discussions to deepen understanding of dental health, Counseling on oral health to elementary school students Result: Dental Health Counseling activities at SD - IT Azzahra Demak were carried out for 2 days. Participants who attended this activity were 37 teachers and 190 elementary school students - IT Azzahra Demak Conclusion: Community service activities in the form of dental health counseling for teachers and students of SD - IT Azzahra Demak took place smoothly and had enormous benefits for increasing knowledge about dental health for elementary school teachers and elementary students. This will certainly improve the degree of dental health, especially for children